The Effect Of Tax Socialisation and Motivation To Pay Tax On Tax Payment Awareness Among Universitas Padjadjaran Students - Adisti Gilang Cempaka; Fauzan Akmal Ramadhan (International Journal of Management and Business Economics, 2026)
This study aims to examine the influence of tax socialisation and motivation to pay tax on tax awareness among university students. A quantitative approach was applied, using primary data by distributing questionnaires to Universitas Padjadjaran students. The sampling technique was carried out by purposive sampling technique. Data were analysed using Multiple Regression Analysis. The findings indicate that tax socialization and motivation to pay tax positively and significantly affect tax awareness among Universitas Padjadjaran students. The study provides for tax authorities, that the synergy between external education through socialization and strengthening internal motivation is crucial in forming a tax awareness culture in the university environment that can lead to tax compliance.